Antenna representation in two-port network scattering parameter - Prakoso, Teguh (Wiley Periodicals, Inc., 2011)
This paper proposes a representation of antenna in two-port network s-parameter, by exploiting the analogy between the antenna and a two-port network, to produce a suitable method for evaluating antennas in system and circuit simulation. Complicated steps required by previous methods to determine an antenna-specific equivalent-circuit and its corresponding resistor, inductor, and capacitor values are avoided. Simulations results obtained for the circuit and system software confirms the validity of the proposed scheme.